Effectiveness and Contribution of Local Taxes to Cirebon Regional Revenue - Al-Hazmi, Raldin Alif (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2024)
One of the cities that has a lot of potential for local revenue (PAD) is Cirebon City. Various events, such as concerts, dramas, entertainment, and national and international exhibitions, are organized in Cirebon City. The entertainment tax target for Cirebon City has increased as a result of the enactment of Law No. 1 Year 2022 on Financial Relations between the Central Government and Local Government. Descriptive quantitative approach methodology was used in this study. PAD of Cirebon City in 2017-2022, projection of entertainment tax revenue, and realization of entertainment tax are the statistical data used in this study. According to the study findings, the entertainment tax of Cirebon City has an effectiveness rate of 72.87% from 2017 to 2022 despite having less stringent requirements and a very low contribution rate of 1.42%. In order to help the Cirebon City Government to maximize the potential of its area to generate tax revenue in accordance with the predetermined objectives, this study intends to provide knowledge related to the analysis of the effectiveness and contribution of entertainment tax. Keywords: Contribution, Effectiveness, Entertainment Tax, Local Tax, Local Revenue.